2017
DOI: 10.1056/nejmoa1615975
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib or Adalimumab versus Placebo for Psoriatic Arthritis

Abstract: The efficacy of tofacitinib was superior to that of placebo at month 3 in patients with psoriatic arthritis who had previously had an inadequate response to conventional synthetic DMARDs. Adverse events were more frequent with tofacitinib than with placebo. (Funded by Pfizer; OPAL Broaden ClinicalTrials.gov number, NCT01877668 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
525
2
32

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 483 publications
(581 citation statements)
references
References 19 publications
22
525
2
32
Order By: Relevance
“…Psoriatic arthritis is an autoimmune disease that affects both joints and the skin. Tofacitinib was found to be superior to placebo in patients with psoriatic arthritis who had previously had an inadequate response to conventional disease modifying agents and TNF inhibitors . Tofacitinib is now approved for this indication (Table ).…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…Psoriatic arthritis is an autoimmune disease that affects both joints and the skin. Tofacitinib was found to be superior to placebo in patients with psoriatic arthritis who had previously had an inadequate response to conventional disease modifying agents and TNF inhibitors . Tofacitinib is now approved for this indication (Table ).…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…A report showed that tofacitinib may lead to the inhibition of the functional effects of IL‐23 on memory T‐cells and suppresses the expression of IL‐23 receptor during the stimulation of lymphocytes . Different studies have reported the effect of tofacitinib on enthesitis in PsA . Although this may not be primary or exclusively driven by affecting IL‐23 secretion, yet we believe that JAKi are unique in their mechanism of action by affecting the production of several cytokine and, in this case, also IL‐23.…”
Section: Pathogenic Role Of Il‐23 In Enthesitis From Clinical Datamentioning
confidence: 82%
“…Example In this hypothetical example targeting at a real clinical trial scenario, we consider designing a two‐arm superiority Phase 3 trial for a new oral drug in a Janus kinase inhibitor class to treat patients with psoriatic arthritis. The design is based on the recently published data from a Tofacitinib (Tofa), a Janus kinase inhibitor compound, psoriatic arthritis Phase 3 study . The primary efficacy endpoint of the trial was the composite binary endpoint ACR20, a measurement of patients' improvement in signs and symptoms, at the three‐month time point.…”
Section: Implementation Examplesmentioning
confidence: 99%